Irregular migrant women and 2030 Agenda - Subiris Moriel, Virginia Belén (European Public & Social Innovation Review, 2024)
Introduction: Currently, migration is recognized as a transversal phenomenon contributing to the achievement of the 2030 Agenda. However, there is a lack of data on migrant women, particularly those in irregular situations. This omission significantly exacerbates the existing gender gap in access to the labor market, knowledge assets, technological development and participation in decision-making process. Methodology: Our methodology involves exploratory-descriptive research conducted over the past decade, from 2015 to 2024. We employed content analysis of reports from 20 key organizations dedicated to migration. Results: reveal a substantial undervaluation of the human capital of irregular migrant women due to the rigid methodologies of the organizations. Discussions: Researchers have to take in consideration that definition, sources data and methodology will affect data invisibility. Since it does not exist, successful policies are not generated on the management of it to achieve the SDGs. Conclusions: This lead to misguided policies for vulnerable women. This paper calls for a commitment of the 2030 Agenda’s motto, “leave no one behind”, emphasizing the urgent and ongoing need for gender-disaggregated data in the digital era. To achieve this, women in irregular situations must be central to social and economic migration policies.